A dynamic hysteresis model based on Landau phenomenological theory of fatigue phenomenon in ferroelectrics. (December 2020) - He, Xuan; Du, Haoyuan; Tong, Zheng; Wang, Dan; Wang, Linxiang; Melnik, Roderick
Abstract: In the current paper, the coupled fatigue hysteretic behaviors in ferroelectric ceramics are modeled by a blending a phenomenological hysteresis model with point defects. The time-dependent phenomenological model is employed to capture the hysteresis loops associated with phase transitions. The fatigue hysteresis is modeled by combining the single-crystal model with time functions. The mechanism of fatigue in ferroelectric ceramics is interpreted as an accumulation of residual polarization in the proposed model. Numerical results of static and dynamic hysteretic behaviors are presented and compared to their experimental counterparts. The capability of the proposed model for capturing the fatigue phenomenon is validated.